Processed CTD data from RV MARIA S. MERIAN cruise MSM119, Reykjanes Ridge - Timo Fleischmann; Achim J Kopf (PANGAEA, 2025)
Physical oceanography data was acquired by a ship-based Seabird SBE911+ CTD-Rosette system onboard Maria S. Merian during research cruise MSM119. The CTD system is comprised of a Seabird SBE911Plus including dual respectively redundant sensor and pump packages. The SBE11plus Deck Unit remains on board in a laboratory and supplies on one hand power to the SBE9plus underwater unit, on the other hand data telemetry between the SBE9plus and a measurement PC. The SBE9plus underwater unit itself holds a pressure sensor and is interfacing with dual SEB3 temperature, SBE4 conductivity and SBE43 oxygen sensors and two SBE5 pumps to provide a pumped water supply past each sensor. The system also carries an optical FLNTU sensor to measure a combinations of back-scattering, turbidity, and chlorophyll-a. To quantify the photo-synthetically active radiation a PAR sensor is installed as well. Hydrographic data were processed to 1 bin resolution (0.04 s) by using SBEDataProcessing software (version 7.22.5). Processing included the removal of obvious outlier. None were found.